Analisis Implementasi Program Takhassus dalam Pembelajaran Kitab Kuning di Pesantren Tebuireng - Moh. Chalilurrosyid; Jasminto Jasminto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Learning the yellow book as a legacy of classical Islamic knowledge is still an important tradition in the world of Islamic boarding schools. In the midst of the development of the era and the challenges of understanding classical Arabic, Tebuireng Islamic Boarding School applies the Takhassus method as a special approach to deepen the ability of students to understand the texts of the yellow book. This study specifically focuses on 1. How is the Takhassus program in learning the yellow book at the Tebuireng Islamic Boarding School? 2. How is the Analysis of the Implementation of the Takhassus Method in Learning the Yellow Book? 3. What are the Inhibiting and Supporting Factors of the Takhassus Method in Learning the Yellow Book? The method used is qualitative research with a field study type. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation of ongoing learning activities. The main informants consisted of teachers and students who were directly involved in the Takhassus program. The results of the study showed that the implementation of the Takhassus program involved a participant selection process, intensive learning scheduling, and a grammar-based learning approach (nahwu and sharaf) and translation. This program was able to improve students' ability to read and understand the book in depth. However, there were several obstacles such as time constraints, variations in students' initial abilities, and the need to improve the quality of teaching staff. In conclusion, the Takhassus program is an effective strategy in improving the quality of yellow book learning in Islamic boarding schools, as long as it is supported by good teaching management and a sustainable program.